(untitled) (The Research of Medical Science Review, 2025)
Objective: To evaluate the initial results of office-based urethral dilatation in improving lower urinary tract symptoms (LUTS) among postmenopausal women, using the International Prostate Symptom Score (IPSS) questionnaire as the primary outcome measure. Methods: This descriptive case series included 135 postmenopausal women with LUTS unresponsive to medical treatment, recruited from the Department of Urology and Transplant Surgery of PAF Hospital Islamabad from 5 July 2024 to 5 January 2025. Patients with urological malignancies, bladder tuberculosis, small capacity bladder, neurogenic bladder, or pelvic prolapse were excluded. All patients underwent a comprehensive evaluation, including history, clinical examination, urine analysis, urine culture, renal function tests, and ultrasound of kidneys, ureters, and bladder (KUB). Office-based urethral dilatation up to 26 French was performed using metallic dilators, followed by flexible cystoscopy to rule out bladder pathology. Follow-up visits were done on day 7, at 6 weeks, 3 months, 6 months, and 1 year during which IPSS scores were recorded. Statistical analysis was conducted using SPSS version 16, with mean ± standard deviation calculated for quantitative variables and frequency percentages for qualitative variables. Results: The mean age of participants was 64.7 years. Significant improvements in IPSS scores were observed at follow-up intervals with mean reduction of 3.4 at initial follow-up, 7.6 at 6 weeks, and 9.4 at 3 months (p < 0.0001). The procedure was well tolerated and no major complications were reported. Comorbid conditions, including diabetes and hypertension were documented. Conclusion: Office-based urethral dilatation revealed significant improvements in LUTS showing reductions in IPSS scores. The procedure proved to be safe, minimally invasive, and effective for this population. Further Recommendation: In future research with larger sample sizes, diverse patient populations, and extended follow-up is recommended to confirm these findings and explore long-term outcomes.